Influence of the point of attachment of two accelerometers on the assessment of squat jump performances - Houel, N.; Faury, A.; Seyfried, D. (International Journal of Computer Science in Sport, 2013)
The aims of this study were to compare the validity of two accelerometers with a force plate and to determine the influence of the sensor`s point of attachment on the assessment of squat jump performances. Nine male subjects performed a number of squat jumps (n = 38) on a force plate, either with a Myotest or Mensense system attached to their hips and backs. For evaluation purposes, two-way ANOVA tests, correlation coefficients and Bland and Altman tests were used to compare the influence between each sensor and the force plate based on the flight time as well as maximal and take off velocities. The obtained results showed that each sensor, the point of attachment on the subject and their interaction significantly influenced the assessment and validity of the flight time as well as maximal and take off velocities. When attached to the subject`s back, the Mensense sensor estimated the flight time with the best validity in comparison to the force plate measurement. On the other hand, the Myotest sensor estimated the maximal velocity with the best validity when it was attached to the subject`s hip. The take off velocity was estimated by both sensors with very low accuracy. It was therefore inferred that the point of attachment of the sensors and the computational software have a direct influence on the assessment of squat jump performances.